Significance of Social Capital as a Resource for Women's Empowerment: An Analysis from Bangladesh Perspective - Ety, Jannatul Ferdous (Society & Sustainability, 2024)
Social capital has been recognized as a route through which empowerment may ensue in a developing nation like Bangladesh. This research investigated the relationship between social capital formation and women's empowerment in Bangladesh. A narrative review was performed to derive conclusions from secondary data for this qualitative study, employing a descriptive research design. Two themes emerged from the findings: the role of social capital in capacity building and the significance of network building as a means of establishing social capital. Firstly, women's participation in social networks increases their likelihood of making strategic decisions regarding themselves and the community. Secondly, women's engagement in self-help projects and credit groups, which are based on women groups, helped them to build their capability in those sectors along with the rise in education and entrepreneurship. However, challenges coming from deeply rooted traditions, conservative religious practices, and family and social values contradict the benefits of social capital women may derive from them. Thus, social capital must be considered for the policies concerning future community development and women's empowerment. This study also provides guidelines for further study with broader scope and systematic studies in the future.